Metagenomic analysis reveals methanogenic and other archaeal genes in the digestive tract of invasive Japanese beetle larvae and associated soil - Helena Avila-Arias; Michael E. Scharf; Ronald F. Turco; Diego J. Jiménez; Audrey Simard; Douglas S. Richmond (Frontiers in Microbiology, 2025)
The linkage between methane emissions and the metabolic activity of archaeal species is broadly established. However, the structural and functional dynamics of this phenomenon within the scarab larval gut and associated host soil environment have not been investigated. In this study, we used shotgun metagenome sequencing to explore the archaeal communities associated with the digestive tract of third instar Japanese beetle (Popillia japonica Newman; Coleoptera: Scarabaeidae) (JB) larvae and its host soil. Our findings showed that both the JB gut compartment (midgut vs. hindgut) and experimental conditions (field vs. manipulative laboratory studies) significantly affect the composition of archaeal taxa. Moreover, gut compartment affected the functional profile. Results revealed an increase of methane metabolism-related taxa and gene sequences in the larval hindgut, supporting the hypothesis that methanogenesis is primarily maintained in that gut compartment. Methane production associated with the JB larval gut takes place primarily via CO2 reduction (~30%) and methanol methanation (4%) pathways. The presence of the same archaeal features in both soil and JB midgut suggests that the JB midgut archaeome may be environmentally sourced, with more tailored selection of the archaeome occurring in the JB hindgut. In turn, we found that JB larval infestation also increases the abundance of at least one methanogenic archaeon, Methanobrevibacter, in infested soil. Results underscore the potential impact of invasive root-feeding scarab larvae on the soil archaeome and highlight their potential contributions to climate change, especially in light of predicted global range expansion for this species.